2022
DOI: 10.1021/acsami.2c06642
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of a Facilely Synthesized MnV2O6 Catalyst on Improving the Low-Temperature Kinetic Properties of MgH2

Abstract: While magnesium hydride (MgH2) has drawn considerable attention as a promising hydrogen storage material, it suffers from sluggish kinetics and high desorption temperature, hindering potential applications. Herein, we show that the hydrogen desorption kinetics of MgH2 can be significantly improved using bimetallic oxide MnV2O6 as the catalyst. A MgH2–MnV2O6 composite was prepared by a high-energy ball milling method. The results showed that the MgH2–MnV2O6 composite can release 5.57 wt % hydrogen within 10 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…As shown in Figure 5a, even after 50 cycles of hydrogen absorption at 150 °C and desorption at 275 °C, the MgH 2 −5 wt % Ni@C composite exhibited excellent reversibility, and the total capacity decay for hydrogen absorption and desorption was only 2.9 and 5.6% after 50 cycles, respectively. Compared with other MgH 2 −catalyst composites, 15,43,56,57 the MgH 2 −5 wt % Ni@C composite in this work exhibits superior cycling stability. We observed the microstructure and phase composition of the MgH 2 −5 wt % Ni@C composite before and after hydrogen absorption/ desorption cycling.…”
Section: ■ Results and Discussionmentioning
confidence: 87%
“…As shown in Figure 5a, even after 50 cycles of hydrogen absorption at 150 °C and desorption at 275 °C, the MgH 2 −5 wt % Ni@C composite exhibited excellent reversibility, and the total capacity decay for hydrogen absorption and desorption was only 2.9 and 5.6% after 50 cycles, respectively. Compared with other MgH 2 −catalyst composites, 15,43,56,57 the MgH 2 −5 wt % Ni@C composite in this work exhibits superior cycling stability. We observed the microstructure and phase composition of the MgH 2 −5 wt % Ni@C composite before and after hydrogen absorption/ desorption cycling.…”
Section: ■ Results and Discussionmentioning
confidence: 87%
“…However, as the reaction conditions change, the corresponding reaction models will also change. [43][44][45] In order to investigate the rate-limiting step of isotherm dehydrogenation, the classical nucleation and growth model, Johnson-Mechl-Avrami (JMA) model, 2,23 is applied to t the experimental data. The equation of the JMA model is…”
Section: Hydrogen De-/absorption Performancementioning
confidence: 99%
“…29–31 For example, Fu et al . 32 found that MnV 2 O 6 catalyzed MgH 2 could discharge 5.57 wt% hydrogen at 250 °C and charge 3.09 wt% hydrogen at 50 °C in 10 min. Lu et al .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous previous studies have shown that the synergistic impact between different elements or phases can further increase the catalytic activity and improve MgH 2 properties. [29][30][31] For example, Fu et al 32 found that MnV 2 O 6 catalyzed MgH 2 could discharge 5.57 wt% hydrogen at 250 °C and charge 3.09 wt% hydrogen at 50 °C in 10 min. Lu et al 33 proved that MgH 2 + ZrO 2 @Nb 2 CTx could release 6.24 wt% hydrogen at 300 °C in 150 s and about 5.69 wt% hydrogen was discharged in 15 min even at 240 °C.…”
Section: Introductionmentioning
confidence: 99%